Properties, applications and thermal investigation of aerogels - Tychanicz, Maria; Smusz, Robert (Advances in Mechanical and Materials Engineering)
Among the variety of products for thermal insulation in industry the aerogel blankets have received significant attention because of their unique properties and wide range of applications. This paper presents the basic properties, fields of application and results of experimental study of Pyrogel XT, which is a type of high temperature aerogel blanket. It is formed of silica aerogel and reinforced with glass fiber batting. In comparison with traditional insulating materials Pyrogel XT is much more efficient thermal insulation with wide temperature range of application (-40÷650ºC). It also has the lowest thermal conductivity of any known solid material. Experimental investigation of thermophysical properties of Pyrogel XT was carried out by using traditional and modern research methods. The traditional method utilized a simplified single-plate Poensgen apparatus. The modern approach was performed on a UnithermTM model 2022 thermal conductivity instrument which uses a guarded heat flow meter method according to ASTM E1530 standard. Results obtained from both devices were compared and analyzed.